Combination of Sodium Bicarbonate (SBC) with Bacterial Antagonists for the Control of Brown Rot Disease of Fruit - Nadia Lyousfi; Chaimaa Letrib; Ikram Legrifi; Abdelali Blenzar; Assia El Khetabi; Hajar El Hamss; Zineb Belabess; Essaid Ait Barka; Rachid Lahlali (Journal of Fungi, 2022)
Simultaneous treatment with antagonistic bacteria Bacillus amylolquefaciens (SF14), Alcaligenes faecalis (ACBC1), and the food additive sodium bicarbonate (SBC) to control post-harvest brown rot disease caused by Monilinia fructigena, and their effect on the post-harvest quality of nectarines were evaluated. Four concentrations of SBC (0.5, 2, 3.5, and 5%) were tested. Results showed that bacterial antagonists displayed remarkable compatibility with different concentrations of SBC and that their viability was not affected. The results obtained in vitro and in vivo bioassays showed a strong inhibitory effect of all treatments. The combination of each bacterial antagonist with SBC revealed a significant improvement in their biocontrol efficacies. The inhibition rates of mycelial growth ranged from 60.97 to 100%. These results also indicated that bacterial antagonists (SF14 or ACBC1) used at 1 × 108 CFU/ mL in combination with 2, 3.5, or 5% SBC significantly improved the control of M. fructigina by inhibiting the germination of spores. Interestingly, disease incidence and lesion diameter in fruits treated with SF14, ACBC1 alone, or in combination with SBC were significantly lower than those in the untreated fruits. In vivo results showed a significant reduction in disease severity ranging from 9.27 to 64.83% compared to the untreated control, while maintaining the appearance, firmness, total soluble solids (TSS), and titratable acidity (TA) of fruits. These results suggested that the improved disease control by the two antagonistic bacteria was more likely due to the additional inhibitory effects of SBC on the mycelial growth and spore germination of the pathogenic fungus. Overall, the combination of both bacteria with SBC provided better control of brown rot disease. Therefore, a mixture of different management strategies can effectively control brown rot decay on fruits.